The Influence of Professional Competence Of Islamic Education Teachers On Behavioral Changes In Al-Husna High School Students, Tangerang City - Abnisa, Almaydza Pratama; Zubairi, Zubairi (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This study aims to determine the effect of professional competency of Islamic education Teachers on changes in the behavior of SMA Al-Husna Tangerang City students. The hypothesis tested states that there is a significant influence of teacher professional competence on changes in the behavior of SMA Al-Husna Tangerang City students. This research was conducted using survey and quantitative descriptive methods. The population in the study were all students of SMA Al-Husna Tangerang City as the target population, totaling 105 students, while the reachable population consisted of 44 students. The research instrument for measuring teacher professional competence uses a questionnaire (questionnaire). Validity is calculated using the product moment correlation technique. Reliability is calculated by Alpha Cronbach formula. The test results show that 39 statement items are declared valid, and the reliability of r count = 0.96. The analysis requirements test is the normality test using the Lilie Fors test and the homogeneity test using the Fisher test. Inferential analysis (Hypothesis Test) with simple regression and correlation analysis. The results of the study concluded as follows: there is a significant influence of teacher professional competence on changes in the behavior of Al-Husna High School students in Tangerang City, with a correlation coefficient = 0.96 at a significance level of 0.05. This means that the hypothesis which states that there is a significant influence between the professional competence of teachers on changes in student behavior is accepted. So that the teacher's professional competency variable (X) makes a contribution (contribution) to the variable changes in student behavior (Y) of 0.96%. This means that the interpretation of the correlation coefficient or the influence of the teacher's professional competence on changes in student behavior is very strong. This research is expected to be useful for improving the quality of student behavior so that they have noble morals. Research shows that the professional competence of teachers has a significant effect on changes in student behavior at SMA Al-Husna Tangerang City. Teachers who have high professional competence are able to inspire and motivate students to behave better in various aspects of life, both at school and outside of school. professional competency of Islamic education Teachers which includes material knowledge, teaching methods, interpersonal skills, class management, and objective assessment plays an important role in shaping student behavior. This research has important implications for the development of education at SMA Al-Husna Tangerang City. Teachers need to continue to improve their professional competence in order to have a positive impact on changes in student behavior. Schools may also consider continuing training and development for teachers to strengthen their professional competency of Islamic education Teachers. It is hoped that the results of this study can contribute to an understanding of the importance of teacher professional competence in achieving positive behavior change in high school students.